The Democratic Deficit and European Union Communication Policy: An Evaluation of the Commission's Approach to Broadcasting - Ward, David (Javnost-The Public, 2001)
The article evaluates European Union broadcasting policy in the context of the democratic deficit. It argues that it is essential to understand the democratic deficit in terms of communicative action, but this entails the question of media policy and specifically broadcasting, as one of the dominant mediums in which citizens participate in public life. In outlining the basic nature of the European Commission's approach to broadcasting, the work employs the concepts of internal and external pluralism heuristically. Applying these two categories to the Commission's decisions on State aid and competition policy, in order to assess how European Union media policy hangs together to form a comprehensive approach to media regulation. It challenges what has become the orthodoxy in reviews of European audiovisual policy and argues that the Commission has adopted a mature sense of the importance of broadcasting in the democratic process. At the same time however, the idea that the democratic deficit can be fruitfully approached through broadcasting initiatives is undermined due to the restricted access the Commission has to the broadcasting sector in the regulatory sphere, where the Member States retain power.